This set of Numerical Methods Multiple Choice Questions & Answers focuses on “Gauss Elimination Method – 2”.

1. Which of the following step is not involved in Gauss Elimination Method?

a) Elimination of unknowns

b) Reduction to an upper triangular system

c) Finding unknowns by back substitution

d) Evaluation of cofactors

View Answer

Explanation: Elimination of unknowns, reduction to an upper triangular system and finding unknowns by back substitution are the primary steps involved in Gauss Elimination.

2. Gauss Elimination Method is well adopted for which of the application?

a) Computer operations

b) Network circuit problems

c) MATLAB operations

d) Telecommunication operations

View Answer

Explanation: Gauss Elimination Method is well adopted for computer operations. It is an effective and fast process.

3. What are the coefficients of the equation obtained during the elimination called?

a) Joints

b) Pivots

c) Calculated coefficients

d) Operative coefficients

View Answer

Explanation: The coefficients of the equation obtained during the elimination are called as pivots.

4. How the transformation of coefficient matrix A to upper triangular matrix is done?

a) Elementary row transformations

b) Elementary column transformations

c) Successive multiplication

d) Successive division

View Answer

Explanation: The transformation of coefficient matrix A to upper triangular matrix is done through elementary row transformations. We will not lead towards the correct answer if we’ll perform transformations in rows as well as columns.

5. How many types of pivoting are there?

a) 2

b) 3

c) 4

d) 5

View Answer

Explanation: There are two types of pivoting, namely, partial and complete pivoting.

6. The modified procedure of complete pivoting is called as ____________

a) Partial

b) Additional

c) Reduced

d) Modified

View Answer

Explanation: The modified procedure of complete pivoting is called as Partial Pivoting.

7. Apply Gauss Elimination method to solve the following equations.

x + 4y – z = -5 x + y – 6z = -12 3x – y – z = 4

a) x = 1.6479, y = -1.1408, z = 2.0845

b) x = 4.0461, y = -1.1408, z = 3.254

c) x = 7.2478, y = -2.586, z = 8.265

d) x = 2.8471, y = 5.5123, z = 2.0845

View Answer

Explanation: x + 4y – z = -5 ………(i)

x + y – 6z = -12 …………………..(ii)

3x – y – z = 4 …………………….(iii)

To eliminate x, operate (ii) – (i) and (iii) – 3(i),

-3y – 5z = -7 ………………………(iv)

-13 + 2z = 19 ………………………(v)

To eliminate y, (v) – (13/3)(iv),

(71/3) z = (148/3)

Now by back substitution,

Z = \(\frac{148}{71}\) = 2.0845

Y = \(\frac{7}{3} – \frac{5}{3}(\frac{148}{71})\)

= \(\frac{-81}{71}\) = -1.1408

X = -5 -4\((\frac{-81}{71}) + (\frac{148}{71})\)

= \(\frac{117}{71}\) = 1.6479

Hence x = 1.6479, y = -1.1408, z = 2.0845.

8. Apply Gauss Elimination method to solve the following equations.

10x – 7y = 3z + 5u = 6 -6x + 8y – z – 4u = 5 3x + y + 4z + 11u = 2 5x – 9y – 2z + 4u = 7

a) u = 1, z = -7, y = 4, x = 5

b) u = 1, z = -7, y = 4, x = 5

c) u = 1, z = -7, y = 4, x = 5

d) u = 1, z = -7, y = 4, x = 5

View Answer

Explanation: 10x – 7y = 3z + 5u = 6 …….(i)

-6x + 8y – z – 4u = 5 ………………….(ii)

3x + y + 4z + 11u = 2 ………………….(iii)

5x – 9y – 2z + 4u = 7 ………………….(iv)

To eliminate x, operate

[(ii) – \((\frac{-6}{10})\) (i)], [(iii) – \(\frac{3}{10}\)(i)] and [(iv) – \(\frac{5}{10}\)(i)]

3.8y + 0.8z – u = 8.6 ……………………(v)

3.1y + 3.1z + 9.5u = 0.2 …………………(vi)

-5.5y – 3.5z + 1.5u = 4 ………………….(vii)

To eliminate y, operate [(vi) – \(\frac{3.1}{3.8}\)(v)], [(vii) – \(\frac{5.5}{3.8}\)(v)],

2.447z + 10.31u = -6.815 …………………(viii)

-2.342z + 0.052u = 16.44 …………………(ix)

To eliminate z operate [(ix) – \((\frac{-2.342}{2.447})\) (viii)] ,

9.924u = 9.924

By back substitution,

u = 1, z = -7, y = 4, x = 5.

9. Apply Gauss Elimination method to solve the following equations.

2x + y + z = 10 3x + 2y + 3z = 18 X + 4y + 9z = 16

a) X = 7, y = -4, z = 5

b) X = 7, y = -9, z = 5

c) X = 5, y = 1, z = -8

d) X = 5, y = 1, z = -3

View Answer

Explanation:

2x + y + z = 10 ………………….(i)

3x + 2y + 3z = 18 ………………..(ii)

x + 4y + 9z = 16 …………………(iii)

To eliminate x, operate (i) – 2(iii), (ii) – 3(iii)

7y + 17z = 22 ……………………(iv)

5y + 12z = 15 ……………………(v)

To eliminate y, operate [(iv) – \(\frac{7}{5}\)(v)]

0.2z = 1

By back substitution,

z = 5

7y = 22 – 85

y= -9

x = 16 + 36 – 45

x = 7

Hence, x = 7, y = -9, z = 5.

10. Apply Gauss Elimination method to solve the following equations.

2x – y + 3z = 9 x + y + z = 6 x – y + z = 2

a) X = 5, y = 14, z = 5

b) X = -13, y = 4, z = 15

c) X = -13, y = 1, z = -8

d) X = 13, y = 1, z = -8

View Answer

Explanation: 2x – y + 3z = 9 ……….(i)

x + y + z = 6 ……………………(ii)

x – y + z = 2 ……………………(iii)

To eliminate x, operate (ii) – (iii)

y = 4

Now, operate (i) – 2(ii),

-3y + z = 3

Now by back substitution,

Z = 15

X + 4 +15 = 6

X = -13.

**Sanfoundry Global Education & Learning Series – Numerical Methods.**

To practice all areas of Numerical Methods, __here is complete set of 1000+ Multiple Choice Questions and Answers__.